Bottom Up-Sharia Formalization in Indonesia’s Nation State - HAEDAR NASHIR (Jurnal Studi Pemerintahan, 2017)
This paper describes the bottom up-Shariah formalization in the Indonesian na- tion-state. The Islamic movement has been fighting for the Islamic Sharia in the provinces of South Sulawesi, West Java, and Aceh. The Islamic Sharia in these areas also had fundamental Islamic political powers such as Syarikat Islam and Masyumi in the past. Based on the facts pre- viously mentioned, this study is carried out by focusing on such three areas. This study used a sociology perspective on religious movements focusing on the study of human social life, groups, and societies. By using the sociology perspective, the aspects may be analyzed interpretatively given that according to Weber, so- ciology is the knowledge that sticks on the interpretative of social actions. The analysis above clearly shows the different dynamics of South Sulawesi, Aceh, and West Java. Aceh has more chance to implement Islamic Sharia through the legislation of the Law, Local Regulation (Perda), and Governor Decree since it leans more in the form of political “present” from the Central Government as the compensation of a prolonged conflict resolution. In South Sulawesi, the move- ment of Islamic Sharia implementation was born naturally through the efforts of various Muslim components which almost entirely and excitedly appeared from its capital province, Makassar (Ujung Pandang). While in the West Java, precise Islamic movement doesn’t move in Bandung, but it grows and develops through the Muslims aspiration and the Regents in some rural area such as Cianjur, Tasikmalaya, Garut, and Indramayu.